Pengaruh Sosial Media Dan Strategi Pemasaran Multikultural Terhadap Perilaku Pembelian Impulsif Gen Z Dalam Industri Fast Fashion - Masrikin Djou Massa; Deri Apriadi (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The purpose of this study is to analyze the effects of social media and multicultural marketing strategies on Gen Z's impulsive buying behavior in the fast fashion industry. Impulsive buying is a phenomenon among Gen Zers, who are digital natives and heavily influenced by content found on various social media platforms, like YouTube, Instagram, and TikTok. In addition, the multicultural marketing strategy used by fast fashion brands is becoming more and more sophisticated, especially in light of the more diverse and international market. This study uses a quantitative approach with a survey of 30 Gen Z respondents, who are between the ages of 18 and 25, who are active on social media and have an inclination to buy fast fashion items on impulse.